The Contents of Sagu: Increasing Pencak Silat Athletes’ Endurance - Gandi, Nadia Hasti; Riswanto, A. Heri; Jalil, Rasyidah (Department of Physical Education, Sport, Health and Recreation, 2023)
Pencak silat is a traditional sport that is identical to a match number using full body contact physical activity. while endurance (VO2max) serves to maintain physical condition during the match so that the body does not experience excessive fatigue. To support the gaining of good endurance, it is necessary to consume many sources of energy. This study aims to determine the effect of the nutritional content of sagu in increasing the endurance of pencak silat athletes. The nutritional content of 100 gram serving of sagu consists of 357 calories, 1.4 grams of protein, 0.2 grams of fat, 85.9 mg of carbohydrates. The sample in this study is 10 pencak silat athletes from Palopo City, which were carried out at the training location at the Palopo Madrasah Tsanawiyah Multipurpose Building and Muhammadiyah Palopo University Sports Field. The method used in data collection is an experiment using a one-group pretest and posttest design and the test instrument used is the Multistage-fitnes test (MFT) running 20 M back and forth. The result of this study is that the nutritional content of sagu is able to increase the endurance of pencak silat athletes without giving any side effects.